2000
DOI: 10.1097/00003246-200004000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between procalcitonin plasma levels and severity of injury, sepsis, organ failure, and mortality in injured patients

Abstract: These data indicate that PCT represents a sensitive and predictive indicator of sepsis and severe MODS in injured patients. Routine analysis of PCT levels seems to aid early recognition of these posttraumatic complications. Thus, PCT may represent a useful marker to monitor the inflammatory status of injured patients at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
158
2
12

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(185 citation statements)
references
References 23 publications
13
158
2
12
Order By: Relevance
“…In local and systemic inflammation, successive monocytic activation is a prerequisite for PCT production (21)(22)(23)(24). PCT serves as a chemo-attractant.…”
Section: Discussionmentioning
confidence: 99%
“…In local and systemic inflammation, successive monocytic activation is a prerequisite for PCT production (21)(22)(23)(24). PCT serves as a chemo-attractant.…”
Section: Discussionmentioning
confidence: 99%
“…PCT seems to be a good marker for monitoring the status of inflammatory reaction in patients suffering from multiple trauma [12], although significant gender differences between men and women have been found [13]. Experiments have shown that hepatic tissue stimulated by TNF-alpha or Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Peak values are observed in the first 24 hours and around the 3 rd day following trauma. High levels of PCT during the first days after injury are believed to be a prognostic factor in severe systemic inflammatory response syndrome (SIRS), infection or multiple organ dysfunction syndrome (MODS) [12][13][14][15][16].…”
mentioning
confidence: 99%
“…Further, ICU length of stay is affected by other variables that may not be reflected in the chart, such as communication and family issues, stress and depression, palliative care and ethical issues, 24-hour presence of a physician, and availability of a unit-specific social worker. 7 Use of the SIRS score in this research is supported by (1) the outcomes of the 2001 consensus conference, 16 (2) research that correlates the presence of SIRS with inflammatory biomarkers, [32][33][34][35] and (3) research that validates its use for predicting outcomes in critically ill patients, including those with acute, life-threatening injuries.…”
Section: Limitationsmentioning
confidence: 92%